2021
DOI: 10.3390/ijerph19010020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Two Instruments for the Correct Allocation of School Furniture in Secondary Schools to Prevent Back Pain

Abstract: Background: Back pain is common in secondary school students. If we adjust the school furniture to the anthropometric characteristics of the pupils, we will improve their posture and reduce back pain. There is a high degree of mismatch between the furniture used by students and that which should be used. The objectives of this research are to discover the degree of mismatch and validate two instruments that allow a correct allocation of the furniture. Methods: The selected sample was 132 secondary students (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…The use of the same furniture by primary school children and adolescents may facilitate the adoption of forced positions and may cause long-term discomfort. This assessment is consistent with findings from a study by Gutiérrez-Santiago et al., 45 who have found a high mismatch between secondary school classroom furniture and the students’ anthropometric dimensions. Panagiotopoulou 46 have also observed that most students do not have furniture appropriate for their anthropometric size.…”
Section: Discussionsupporting
confidence: 92%
“…The use of the same furniture by primary school children and adolescents may facilitate the adoption of forced positions and may cause long-term discomfort. This assessment is consistent with findings from a study by Gutiérrez-Santiago et al., 45 who have found a high mismatch between secondary school classroom furniture and the students’ anthropometric dimensions. Panagiotopoulou 46 have also observed that most students do not have furniture appropriate for their anthropometric size.…”
Section: Discussionsupporting
confidence: 92%